Progressive muscle weakness due to lumbar disc herniation in pregnancy: A case report - Gregor Rečnik (Acta Medico-Biotechnica, 2021)
Purpose: Low back pain with radiculopathy caused by lumbar disc herniation is a rare presentation in pregnancy. Appropriate management is based on helping the gravida, while protecting her unborn offspring.Case report: A case of a 35–year–old pregnant woman in the 15th week of pregnancy with disabling pain and progressive motor weakness due to L4–L5 disc herniation is presented. Surgical decompression was performed with an aim to alleviate disabling pain and improve muscle strength.Conclusions: Treatment of disc herniation in pregnancy is conservative in the majority of cases. In the rare likelihood of permanent neurologic sequelae, surgical decompression is indicated, taking into account the specific physiologic condition of pregnancy.